1999
DOI: 10.1046/j.1365-2427.1999.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological connectivity, and the exchange of organic matter and nutrients in a dynamic river–floodplain system (Danube, Austria)

Abstract: Summary 1. The relationship between hydrological connectivity, and the exchange processes of suspended sediments, organic matter and nutrients (NO3‐N) was investigated in a dynamically connected river–floodplain segment of the Danube over a 15‐month period in 1995 and 1996 in the Alluvial Zone National Park, Austria. 2. Based on water level dynamics and water retention times, three phases of river–floodplain connectivity were identified: disconnection (phase I), seepage inflow (phase II) and upstream surface c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
410
3
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(451 citation statements)
references
References 32 publications
18
410
3
4
Order By: Relevance
“…Ca 2+ concentrations could thus be considered as indicator of groundwater inputs, however the local concentrations in the main channel have to be measured to draw valid conclusions. Similar differences between connected and disconnected sites were described in the Danube floodplain (Tockner et al, 1999;Weigelhofer et al, 2015). As in a former study on the Rhône River (Golterman and Meyer, 1985), pH decreased in downstream sections.…”
Section: Patterns In Physico-chemical Variablessupporting
confidence: 84%
See 2 more Smart Citations
“…Ca 2+ concentrations could thus be considered as indicator of groundwater inputs, however the local concentrations in the main channel have to be measured to draw valid conclusions. Similar differences between connected and disconnected sites were described in the Danube floodplain (Tockner et al, 1999;Weigelhofer et al, 2015). As in a former study on the Rhône River (Golterman and Meyer, 1985), pH decreased in downstream sections.…”
Section: Patterns In Physico-chemical Variablessupporting
confidence: 84%
“…The location of the interface between the oxic and the anoxic layer is known to have a major impact on trace metal burial or remobilisation (Merz et al, 2009). Another possible mechanism is the scavenging of metals by accumulation on autochthonous organic matter, the availability of which increases with increasing of water residence time (Ahearn et al, 2006;Hein et al, 2004;Noe and Hupp, 2009;Tockner et al, 1999). Reservoirs along a river could have similar effects as they increase the residence time of water.…”
Section: Trace Metal Spatial Distribution and Partitioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also observed that particulate material (N and P) was to a great extent retained in sediments during high flood and vegetation periods and then released in the fall season (SandJensen 1998;Schulz and Gucker 2005). Tockner et al (1999) found that the Danube floodplain close to Vienna behaved as a trap for POM, whereas it exported DOM and very coarse particles. These findings were widely applicable to N, P, and C dynamics in the Uzlina-Isac complex.…”
Section: Particle Dynamicsmentioning
confidence: 91%
“…The TP-Chl a relationship was generally a linear function (Nicholls and Dillon, 1978;Schindler, 1978;Brown et al, 2000). However, in the lotic waters associated with river, Chl a was usually found to be influenced more strongly by water flow than nutrients (Pace et al, 1992;Tockner et al, 1999a;Lewis et al, 2000). The distinct relationships of log 10 TP-log 10 Chl a in five types of Yangtze lakes are compared (Fig.…”
Section: Macroinvertebratesmentioning
confidence: 99%